Rethinking law and religion - Sandberg, Russell (United Kingdom: Edward Elgar Publishing Limited, 2024)
'This incisive book delineates the development of Law and Religion as a sub-discipline, critically reflecting on the author's own role in constructing the field. It develops a subversive social systems theory in order to take both law and religion seriously and to challenge them equally. Russell Sandberg crafts a new agenda for academic scrutiny of the interaction between religion and the law. Sandberg criticises scholarship to date for focusing on the legal regulation of religion, which reduces the field to an academic sub-discipline in Law Schools. Instead, Sandberg argues for a re-conceptualisation of Law and Religion as an interdisciplinary interaction, comparing it to fields such as legal history and legal geography. He contends that Law and Religion should take on a critical perspective, interrogating the content, nature and purpose of law, and drawing from literature on law and race and law and gender. Provocative, personal and sometimes surprising,'Rethinking Law and Religion' is an illuminating read for students and scholars of law and society, legal theory, and sociology of law and philosophy.'-- Publisher's website.
Puan Shaizimah Badzri/ Ketua Perpustakaan Undang-Undang/ shai@ukm.edu.my/ 0389216393/ OC/ Areesh Education & Trading
Includes bibliographical references and index.
Keywords: Religion and law -- England; Religion and law -- Wales; Religious law and legislation; Law -- Study and teaching -- England